Masa Depan Gas Alam dan Ekonomi Jerman dalam Konstelasi Perang Rusia-Ukraina - Muhammad Andryan Juliardy (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2023)
This paper focuses on the implications of the Russia-Ukraine war on Germany's dependence on natural gas supplies imported from Russia, which affects the German economy. Through the theory of dependency, we will analyze whether energy-dependent relationships cause great losses when relations between countries run into problems and how Germany responds to this situation. Russia is currently trying to take control of Ukraine and has begun a military invasion. Meanwhile, Germany, which is a member of the European Union, is experiencing pressure from the European Union to sanction Russia in the form of a natural gas embargo. Losses can be experienced by Germany due to restrictions on the supply of natural gas energy from Russia which affect the productivity of its industry because the German industry is based on natural gas energy imported from Russia. This study shows that Germany is dependent on natural gas energy cooperation fromRussia. This dependence affects the economic stability of the German state and Germany's political relations with the European Union. So Germany is looking for ways to not depend on natural gas products and switch to renewable energy. Although at first, it was very difficult for Germany to decide to sanction a natural gas embargo against Russia, Germany decided that it was willing and ready to embargo Russia. This research uses qualitative methodology by means of a literature study to obtain data and information. It is interesting to discuss this topic because of the complexity between Germany towards Russia and the European Union in importing natural gas for the benefit of Germany's economic development. Keywords: Germany; Russia; economy; natural Gas; dependency REFERENCES Anderson, R. J. (2008). Europe's Dependence on Russian Natural Gas: Perspectives and Recommendations for a Long-term Strategy. GEORGE C MARSHALL CENTER APO AE 09053 EUROPEAN CENTER FOR SECURITY STUDIES. BDEW. 2019. “Energy Market Germany 2019.” BDEW Bundesverband der Energie- und Wasserwirtschafte. Bhattarai, U., Maraseni, T., & Apan, A. (2022). Assay of renewable energy transition: A systematic literature review. Science of The Total Environment, 155159. Bros, A., Mitrova, T. and Westphal, K. (2017). German-Russian Gas Relations A Special Relationship in Troubled Water. https://www.swpberlin.org/publications/products/research_papers/2017RP13_wep_EtAl.pdf. Diakses pada 18 Oktober 2022. Bundesnetzagentur.de. “Bundesnetzagentur - Aktuelle Lage Gasversorgung - Gasimporte in GWh/Tag,” 2022. https://www.bundesnetzagentur.de/DE/Gasversorgung/aktuelle_gasversorgung/_svg/Gasimport e/Gasimporte.html?nn=1077982. Egan, M. (2022, February 24). Why the Russian invasion will have huge economic consequences for American families. CNN. https://www.cnn.com/2022/02/16/economy/russia-ukraineeconomy-inflation/index.html. Diakses pada 27 Oktober 2022. Eia.gov. (2022). International - U.S. Energy Information Administration (EIA). https://www.eia.gov/international/overview/country/RUS . Diakses pada 28 Oktober 2022. Emmott, R. (2022). EU agrees another 500 million euros for Ukrainian arms. Reuters. https://www.reuters.com/world/europe/eu-seeks-keep-up-support-ukraine-despite-economic damage-2022-07-18/. Diakses pada 23 Oktober 2022. Fouquet, R. Path dependence in energy systems and economic development. Nat Energy 1, 16098 (2016). https://doi.org/10.1038/nenergy.2016 98 . Diakses pada 28 Oktober 2022. Gehrke, Laurenz, and Hans. “Scholz: Russian Energy Ban Would Mean European Recession.” POLITICO. POLITICO, March 23, 2022. https://www.politico.eu/article/olaf-scholz-warns against-russia-energy-embargo/. Diakses pada 29 April 2023. Graabak, I., Korpås, M., Jaehnert, S. and Belsnes, M. (2019). Balancing future variable wind and solar power production in Central-West Europe with Norwegian hydropower. Energy, 168, pp.870–882. doi:10.1016/j.energy.2018.11.068. Diakses pada 15 November 2022. IMF. (2022). The Economic Impacts on Germany of a Potential Russian Gas Shutoff. https://www.imf.org/en/Publications/WP/Issues/2022/07/18/The-Economic-Impacts-on Germany-of-a-Potential-Russian-Gas-Shutoff-520931 . Diakses pada 29 Oktober 2022. Korovkin, V., & Makarin, A. (2019, June 18). Conflict and Inter-Group Trade: Evidence from the 2014 RussiaUkraine crisis. SSRN. https://papers.ssrn.com/sol3/papers.cfm?abstract_id=3397276. Diakses pada 25 Oktober 2022. Krastev, I., & Leonard, M. (2022, February 9). The crisis of European security: What Europeans think about the war in Ukraine. ECFR. https://ecfr.eu/publication/the-crisis-of-european securitywhat-europeans-think-about-the-war-in-ukraine/. Diakses pada 24 Oktober 2022. Lan, T., Sher, G., & Zhou, J. (2022). The economic impacts on Germany of a potential Russian gas shutoff. IMF Working Papers, 2022(144). Lanktree, G. (2022, February 26). Businesses in Britain, EU brace for impact of Ukraine conflict. POLITICO. https://www.politico.eu/article/businesses-in-britain-and-europe-brace-forimpact of-ukraine-conflict/. Diakses pada 28 Oktober 2022. Oecd.org. (2022). Germany Economic Snapshot - OECD. https://www.oecd.org/economy/germany economic-snapshot/ . Diakses pada 29 Oktober 2022. Reuters. “Factbox: What Happens If Russia Turns off Gas to Germany?” Reuters. Reuters, April 2022. https://www.reuters.com/business/energy/what-happens-if-russia-turns-off-gas-flows germany-2022-03-29/#: :text=REUTERS%2FMaxim%20Shemetov.&text=Russia%20accounted%20for%2055 %25%20of,Russian%20supplies%20before%20mid%2D2024. Diakses pada 4 May 2023. Spänhoff, B. (2014). Current status and future prospects of hydropower in Saxony (Germany) compared to trends in Germany, the European Union and the World. Renewable and Sustainable Energy Reviews, 30, pp.518–525. doi:10.1016/j.rser.2013.10.035. Diakses pada 15 November 2022. The New York Times. “The End of the (Pipe)Line? Germany Scrambles to Wean Itself off Russian Gas (Published 2022),” 2023. https://www.nytimes.com/2022/04/06/world/europe/germany gas-russia-ukraine.html. Diakses pada 29 April 2023. Thomas, L., & Strupczewski, J. (2022, February 25). Ukraine crisis will hit economy but EU is ready, officials say. Reuters. https://www.reuters.com/markets/europe/eu-ready-take-economicpain imposing-sanctions-russia-2022-02-25/. Diakses pada 24 Oktober 2022. Welle, Deutsche. “German Energy Crisis: Surviving Winter without Russia.” dw.com. Deutsche Welle, September 22, 2021. Https://www.dw.com/en/germanys-energy-crisis-surviving winter-without-russia/a-59258986. Diakses pada 29 April 2022. Welle, Deutsche. “Uni Eropa Sepakat Jatuhkan Sanksi Baru Kepada Rusia.” dw.com. Deutsche Welle, June 2022. https://www.dw.com/id/eu-sepakati-sanksi-baru-zelenskyy berterimakasih/a-61994105. Diakses pada 24 Oktober 2022. Wiseman, P. (2022, March 2). Economic dangers from Russia's invasion ripple across Globe. AP NEWS. https://apnews.com/article/russia-ukraine-vladimir-putin-coronavirus pandemicbusiness-health-9478a9825c9abfde5f6505bd34b2998c. Diakses pada 21 Oktober 2022. Worldbank.org. (2015). Energy imports, net (% of energy use) - Germany | Data. https://data.worldbank.org/indicator/EG.IMP.CONS.ZS?locations=DE. Diakses pada 18 Oktober 2022. Zukunft Gas. (2022).